PENGARUH LATIHAN KELENTUKAN TERHADAP HASIL TENDANGAN NARYO CHAGI PADA ATLET CADET PUTRA SAVIC TAEKWONDO CLUB LAMPUNG - Rinalfi, Mohamad Ridho; Nureva, Nureva; Sari, Yohana Bella Christian (STKIP Al Islam Tunas Bangsa, 2025)
Savic Taekwondo Club Lampung athletes, especially male cadet sector, had not master on reaching good target when they did Naryo Chagi kick. The Athletes had not proper flexibility, so that they struggled to reach higher target when do naryo chagi kick. To gain that ability, then special treatment was needed. This research goal was to know the influence of flexibility trainings to the outcome of naryo chagi kick for cadet male athlete in Savic Taekwondo Club Lampung. This research was experimental methode research, with 40 persons population and 15 athletes that fullfiled as samples using purposive sampling tehnicque, that one of the terms was they had to be cadet category (12-14 y.o). The instrument test was kicking to the sand sack with validity score was that r arithmetic > r table and the reliability score was 0,654. It was using quantity testment tehnicque for data analysis using SPSS 26 aplication. The result could be concluded that there was influence doing flexibility trainings to the outcome of naryo chagi kick for cadet male athlete in Savic Taekwondo Club Lampung.